EFFICACY OF IVERMACTIN AGANIST SOME NATURALLY ACQUIRED GASTRO-INTESTINAL PARASITIC INFECTION IN MULES - Saleem, Amir n. (The Iraqi Journal of Veterinary Medicine, 2022)
The activity of a single subcutaneous injection of ivermectin at dose of 200 mcg/kg of body weight was evaluated against naturally acquired gastro-intestinal parasites in mules. Faecal samples were examined at the time of treatment and weekly thereafter up to 4 weeks. Results indicated that invrmectin was highly effective (100%) against Oxyuries equi, Strongyloides westeri, Tristostronglus axei, Trichhonema spp., and Strongylus spp. as judged one week after ivermectin administration. Complete elimination of Parascaris equorum eggs occurred two weeks after treatment. In contrast, ivermectin was not effective against the tape worms, Anoplocephala spp.. Infected animals had low levels of haemoglobin and red blood cells counts and an elevated packed cell volume, white blood cells and erythrocyte sedimentation rate. These values returned to normal values 21 days post treatment. No adverse reaction was recorded in the treated animals.